2015
DOI: 10.1042/bj20150660
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 3 indirectly modulates tubulin acetylation

Abstract: Histone deacetylase 3 removes acetyl groups from lysine residues, thereby modifying protein function. It is found in both the nucleus and the cytoplasm. We have discovered that it can indirectly deacetylate tubulin, a cytoplasmic protein that forms microtubules, thus modifying the microtubule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…HDAC3 was found in the nucleus and cytoplasm of different cell types (Longworth & Laimins, ; Takami & Nakayama, ). It has been reported that HDAC3 could form a well‐characterized protein complex with the NCoR (nuclear receptor co‐repressors) or homologous SMRT (silencing mediator of retinoic and thyroid receptors) to control the transcriptional activity (Bacon et al, ; Karagianni & Wong, ). Longworth et al also reported that HDAC3 localizes to the plasma membrane and forms a complex with c‐Src to regulate its activity in HFK + 31 cells (Longworth & Laimins, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HDAC3 was found in the nucleus and cytoplasm of different cell types (Longworth & Laimins, ; Takami & Nakayama, ). It has been reported that HDAC3 could form a well‐characterized protein complex with the NCoR (nuclear receptor co‐repressors) or homologous SMRT (silencing mediator of retinoic and thyroid receptors) to control the transcriptional activity (Bacon et al, ; Karagianni & Wong, ). Longworth et al also reported that HDAC3 localizes to the plasma membrane and forms a complex with c‐Src to regulate its activity in HFK + 31 cells (Longworth & Laimins, ).…”
Section: Discussionmentioning
confidence: 99%
“…αTAT1 was identified to be the major α‐tubulin acetyltransferase (Kalebic et al, ; Shida, Cueva, Xu, Goodman, & Nachury, ). Recently, Bacon et al found that blocking HDAC3 activity modulates tubulin acetylation in the human prostate cancer line PC3 (Bacon et al, ). Likewise, we previously showed that the acetylation levels of α‐tubulin were dramatically increased in mouse oocytes depleted of HDAC3 (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, by controlling the p300 activity, SIRT2 could have an impact on the activity as well as the localization of HDAC6. HDAC3 has also been reported to indirectly control the state of α-tubulin K40 acetylation [84]. HDAC3 has also been reported to indirectly control the state of α-tubulin K40 acetylation [84].…”
Section: Regulation Of α-Tubulin K40 Acetylationmentioning
confidence: 99%
“…This post translational modification is a hallmark of stability because it increases mechanical resilience to ensure the persistence of long-lived microtubules (Xu et al, 2017b) (Janke and Montagnac, 2017). Its downregulation, resulting from either HDACs inhibition or GSK3β activation, has been correlated to microtubule dynamics alteration in different cell types (Garza et al, 2018) (Bacon et al, 2015) (Qu et al, 2017). In these cells, Dock5 acts as a key signaling adaptor that brings Akt into the vicinity of GSK3β, allowing it to phosphorylate GSK3β on serine 9 and inhibit its activity (Ogawa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%